Low-intensity cattle grazing is better than cattle exclusion to drive secondary savannas toward the features of native Cerrado vegetation - Durigan, Giselda; Pilon, Natashi A.L.; Souza, Flaviana M.; Melo, Antônio C.G.; Scorzoni, R. Danilo [UNESP]; Souza, Silvana C.P.M. (Wiley, 2022)
Although livestock have been historically associated with land conversion and biodiversity loss, well-managed cattle grazing has been reported to contribute to conservation of open ecosystems. Knowing the balance between positive and negative effects of livestock (presence or exclusion) on different ecosystems is, therefore, crucial to support management decisions. We conducted an experiment in a secondary savanna with exotic grasses, used as pasture, to assess the effect of cattle presence in low density and cattle exclusion (in paired plots) on the trajectory of these ecosystems. Richness, composition and structure of the woody community, and exotic grass cover and biomass were compared between treatments in the beginning of the experiment and after 7 years. At the end of the experiment, we also compared composition, richness, and density of the native ground layer. We verified that (a) cattle exclusion accelerates the undesirable woody encroachment, changes the species composition and leads to huge grass fuel accumulation, while (b) cattle grazing/browsing hinders changes in savanna structure and composition and reduces the exotic grass cover and biomass, thus favoring native herbaceous plants. By decreasing the grass biomass, cattle grazing also reduces the system flammability and, therefore, the risk and intensity of wildfires. Together, the positive effects of cattle presence and the negative effects of cattle exclusion lead to the conclusion that cattle should be maintained in these systems. Low-intensity cattle grazing limits woody and exotic grass invasion, improves native forb biodiversity, and help to maintain composition and structural features of secondary savannas of the Cerrado. Abstract in Portuguese is available with online material.
Keywords: Brazilian savanna; cattle management; conservation; exotic grasses; natural regeneration; sustainable use; woody encroachment